2020
DOI: 10.3390/s20051340
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classification Method for a Driver’s Cognitive Stress Level by Transferring Interbeat Intervals of the ECG Signal to Pictures

Abstract: In this study, a novel classification method for a driver's cognitive stress level was proposed, whereby the interbeat intervals extracted from an electrocardiogram (ECG) signal were transferred to pictures, and a convolution neural network (CNN) was used to train the pictures to classify a driver's cognitive stress level. First, we defined three levels of tasks and collected the ECG signal of the driver at different cognitive stress levels by designing and performing a driving simulation experiment. We extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Regarding the 2-level stress classification, we can observe that our best-performing model achieves state-of-the-art accuracy, while using a 3 s time window instead of 10 s, and automatically learned representations instead of handcrafted ones. With respect to the 3-level stress classification, our best-performing model exhibits a margin of 9.25% from the works of [ 34 , 44 ]. Factors that lead to this difference are the fact that [ 44 ] leverages multiple signals and [ 34 ] uses a much wider time window of 25 s, as well as the fact that their models are being trained and evaluated on other (non-public) datasets.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the 2-level stress classification, we can observe that our best-performing model achieves state-of-the-art accuracy, while using a 3 s time window instead of 10 s, and automatically learned representations instead of handcrafted ones. With respect to the 3-level stress classification, our best-performing model exhibits a margin of 9.25% from the works of [ 34 , 44 ]. Factors that lead to this difference are the fact that [ 44 ] leverages multiple signals and [ 34 ] uses a much wider time window of 25 s, as well as the fact that their models are being trained and evaluated on other (non-public) datasets.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, instead of using the one-dimensional input of the raw ECG measurements, other approaches transform the signal to two dimensional images that they later feed to 2D CNN models [ 34 , 35 ]. Kang et al.…”
Section: Related Workmentioning
confidence: 99%
“…The abnormal values outside the IBI normal ranges (6–1.2 s) were removed. Then, the descriptive statics were calculated, such as range, minimum, and maximum values, and the time interval of the inter-beat interval was divided into 28 intervals according to the distribution of the inter-beat intervals as discussed in [ 35 ]. Second, a column vector was created for each inter-beat interval and assigned 1 to the interval in which the inter-beat belongs and 0 for the remaining elements.…”
Section: Proposed Stress Image-based Detection Modelmentioning
confidence: 99%
“…They compared the accuracy of this approach with the ANN method using time-domain features (mean IBI and root mean squared difference of adjacent IBIs (RMSSD), and standard deviation of IBIs (SDNN)). They found that the accuracy of the new approach was more accurate than the ANN method, which has been frequently used in recent researches [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active driver status monitoring has been a major research topic for a long time, as it has a significant impact on road safety and accident statistics. Various physiological sensors based on electrocardiogram (ECG) and electroencephalogram (EEG) are nowadays frequently used in numerous studies [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%